Residue soil unfired ceramsite and preparation method thereof
By using slag, gelling materials and admixtures to prepare slag granules, combined with hydrothermal curing technology, the problems of complex process and high energy consumption of slag granules are solved, and efficient resource utilization of slag and slag granules are achieved. Performance improvement.
Patent Information
- Application Number
- CN202411760456.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the process of slag firing ceramics is complex and has high energy consumption, making it difficult to achieve large-scale resource production.
Ceramite is prepared by slag, gelling materials, auxiliary materials and admixtures (active agents, activaters, early strength agents, dehydrating agents, separating agents, homogenizing agents). By extruding and granulating the shell material, the shell material is combined with Hydrothermal curing technology to achieve efficient resource utilization of slag.
It has achieved efficient resource utilization of slag, and prepared ceramic granules with high pressure strength and low water absorption, which has reduced production costs and energy consumption and promoted the resource disposal of slag.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to unburned ceramsite and a preparation method thereof. Background Art
[0002] Patent CN104710156B proposes a rail shield slag unburned and unsteamed ceramsite and its preparation method, using shield slag as the main material, combined with cement, lime, desulfurized gypsum, fly ash and other materials to make ceramsite, the slag controls the moisture content below 5%, and the particle size is below 0.16mm, but the process is relatively complicated and the process cost is high. Patent CN114716255A proposes a shield slag fired ceramsite modifier and shield slag sintering ceramsite method, using urea formaldehyde resin, calcium carbonate, calcium sulfate, bentonite to make the modifier, and then adding the modifier to the shield soil to stir to form improved slag, and then making raw material balls and firing to obtain ceramsite. During the firing process, it is necessary to preheat first, control the heating rate and fire at a high temperature of 1150℃ to obtain ceramsite products. The process is relatively complicated and the energy consumption is high, which is not conducive to large-scale resource production. Summary of the invention
[0003] One of the purposes of the present invention is to provide a slag unburned ceramsite, which is prepared from slag as the main raw material and various types of solid waste. The specific technical solution is: A kind of slag unburned ceramsite comprises an inner core and a coating shell, wherein the inner core comprises a mixture and an admixture.
[0004] Further, the admixture accounts for 1%-10% of the weight of the mixture. Exemplarily, the admixture accounts for 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the weight of the mixture.
[0005] Preferably, the admixture accounts for 2%-8% by weight of the mixture.
[0006] Furthermore, the mixture includes: slag, cementitious materials, and auxiliary materials.
[0007] Furthermore, the admixtures include: an activator, an activator, an early strength agent, a dehydrating agent, a separating agent and a homogenizing agent.
[0008] Preferably, the admixture includes the following components in parts by weight: 20-85 parts of active agent, 1-15 parts of activator, 1-12 parts of early strength agent, 0.5-10 parts of dehydrating agent, 0.5-8 parts of separating agent, and 0.1-7 parts of homogenizing agent.
[0009] Exemplarily, the active agent is in the range of 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts or any two of them; the stimulator is in the range of 1 part, 5 parts, 10 parts, 15 parts or any two of them; the early strength agent is in the range of 1 part, 5 parts, 8 parts, 10 parts, 12 parts or any two of them; the dehydrating agent is in the range of 0.5 parts, 1 part, 5 parts, 10 parts or any two of them; the separating agent is in the range of 0.5 parts, 1 part, 5 parts, 8 parts or any two of them; the homogenizing agent is in the range of 0.1 parts, 1 part, 3 parts, 5 parts, 7 parts or any two of them.
[0010] Further preferably, the admixture includes the following components in parts by weight: 25-80 parts of active agent, 2-8 parts of activator, 2-8 parts of early strength agent, 1-5 parts of dehydrating agent, 1-5 parts of separating agent, and 1-5 parts of homogenizing agent.
[0011] Furthermore, the active agent is selected from one or more of silica fume, high calcium fly ash and quartz sand.
[0012] Preferably, the active agent is selected from one or more of high-calcium fly ash and quartz sand.
[0013] Furthermore, the particle size of the active agent is 200-1000 mesh.
[0014] Preferably, the particle size of the active agent is 300-400 mesh.
[0015] Furthermore, the activator is selected from one or more of sodium sulfate, sodium hydroxide, calcium hydroxide and sodium silicate.
[0016] Preferably, the activator is selected from one or both of sodium hydroxide and sodium silicate.
[0017] More preferably, the activator is a mixture of sodium hydroxide and sodium silicate.
[0018] Further, the weight ratio of sodium hydroxide to sodium silicate in the activator is 1:0.5-3.5. Exemplarily, the weight ratio of sodium hydroxide to sodium silicate is 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or a range consisting of any two thereof.
[0019] Preferably, the weight ratio of sodium hydroxide to sodium silicate in the activator is 1:1-2.
[0020] Furthermore, the early strength agent is selected from one or more of gypsum, desulfurized gypsum, calcium carbonate, triethanolamine, and calcium aluminate.
[0021] Furthermore, the dehydrating agent is selected from one or more of polyacrylamide, potassium aluminum sulfate dodecahydrate, aluminum chloride, and polyferric chloride.
[0022] Furthermore, the separating agent is selected from one or more of tartaric acid, sodium alkylphenol polyate, sodium methyl silicate, and calcium stearate.
[0023] Furthermore, the leveling agent is selected from one or more of cellulose ether, lignin, naphthalenesulfonate formaldehyde condensate, and polycarboxylic acid.
[0024] Furthermore, the preparation method of the admixture is: after mixing the activator, the stimulator, the early strength agent, the dehydrating agent, the separating agent and the homogenizing agent, the mixture is ground to a particle size of ≤0.075 mm.
[0025] Further, the mixture includes the following components in parts by weight: 10-80 parts of slag, 5-20 parts of cementitious materials, and 10-30 parts of auxiliary materials. Exemplarily, the slag is in the range of 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, 60 parts, 70 parts, 80 parts, or any two of them; the cementitious materials are in the range of 5 parts, 10 parts, 15 parts, 20 parts, or any two of them; the auxiliary materials are in the range of 0 parts, 10 parts, 20 parts, 30 parts, 40 parts, 50 parts, or any two of them.
[0026] Furthermore, the slag is selected from one or more of shield slag, engineering slag, building slag, and river and lake silt.
[0027] Furthermore, the cementitious material is selected from one or more of silicate cement, sulphoaluminate cement, slag cement, carbide slag, quicklime and waste lime.
[0028] Furthermore, the auxiliary material is selected from one or more of fly ash, quartz tailings, silica mud, slag, concrete powder, metakaolin, porcelain clay, and volcanic ash soil.
[0029] Another object of the present invention is to provide a method for preparing unburned ceramsite from slag, comprising the following steps: S1. Mix slag, cementitious materials, auxiliary materials and admixtures to obtain internal core materials; mix cementitious materials and auxiliary materials to obtain coating shell materials; S2. The internal core material is made into a ceramsite core by extrusion granulation or disc granulation molding process; S3, coating the coating shell material on the surface of the ceramsite core to obtain a ceramsite green body; S4. The unburned expanded clay pellets are obtained through curing.
[0030] Furthermore, in step S1, the coating shell material accounts for 1-5% of the weight of the internal core material.
[0031] Further, in step S1, in the coating shell material, the weight ratio of the gelling material to the auxiliary material is (1-5): (5-8); illustratively, the weight ratio of the gelling material to the auxiliary material is 1:5, 1:6, 1:7, 1:8, 3:5, 3:6, 3:7, 3:8, 5:5, 5:6, 5:7, 5:8 or a range consisting of any two of them.
[0032] Furthermore, S1 also includes the following steps: the internal core material is sent to a digestion bin for digestion, and then enters a powder mixing system for dispersion.
[0033] Furthermore, the digestion time is 1-3h.
[0034] Furthermore, in step S2, 1-20% of water is added to facilitate better granulation.
[0035] Furthermore, in step S4, the curing includes pre-curing and autoclave curing.
[0036] Furthermore, in step S4, the pre-curing temperature is 20-80°C, the curing humidity is 20-95%, and the curing time is 1-24h.
[0037] Furthermore, in step S4, the reaction temperature of the autoclave curing is 150-200° C., the reaction pressure is 0.5-1.0 MPa, and the reaction time is 5-8 h.
[0038] The beneficial effects of the present invention are: 1) The present invention uses a mixture (slag, gel material, auxiliary material) and an admixture to prepare the inner core of ceramsite. The admixture is compounded from an activator, an activator, an early strength agent, a dehydrating agent, a separating agent and a homogenizing agent, which can release the bound water inside the slag, make the slag, auxiliary material and gel material evenly dispersed, and release the internal activity of the slag, thereby obtaining ceramsite with high cylinder pressure strength and low water absorption, and realizing efficient resource utilization of slag.
[0039] 2) The present invention adds admixtures to disperse the slag raw materials. Through the joint action of the early strength agent, dehydrating agent, separating agent and homogenizing agent, the bound water inside the slag is released, so that the slag particles and the auxiliary materials and the cementitious materials are evenly dispersed, the particle size distribution of the mixture is effectively controlled, and the internal activity of the slag is further released; combined with the effects of the activating agent and the stimulating agent, on the one hand, the siliceous activity inside the slag is supplemented to provide seeds for the hydrothermal synthesis at the back end, which can accelerate the synthesis of the hydrothermal products and thus improve the product performance; on the other hand, the siliceous activity inside the slag is promoted by the stimulating agent, so that the inert silicon dioxide inside the slag that is not easy to participate in the reaction is stimulated, the activity of the slag is improved from the raw material end, and the prepared ceramsite has high cylinder compressive strength and low water absorption rate. The obtained ceramsite can be used as a high-quality building material product, effectively realizing the efficient resource utilization of slag.
[0040] 3) The present invention directly utilizes slag and realizes slag modification in combination with admixtures, without the need for excessive treatment of the slag. By regulating the overall process equipment and conditions at the back end, high-strength slag ceramsite is prepared using the non-burning technology, thereby realizing large-scale resource utilization of slag, promoting the resource disposal of slag, and proposing a new path for the solid waste resource utilization of urban slag.
[0041] 4) The present invention utilizes fly ash, slag and other solid wastes to coordinately dispose of slag, and utilizes hydrothermal solidification technology to improve the dispersion reaction of materials through methods such as digestion and powder mixing, coating and shelling, and pre-curing, thereby improving the strength of the ceramsite green body, increasing the degree of hydrothermal reaction of the product, controlling the production cost, reducing the energy consumption of the entire process, and preparing building materials with excellent performance. DETAILED DESCRIPTION
[0042] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0043] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0044] A method for preparing unburned clay ceramsite comprises the following steps: S1. Mix slag, cementitious materials, auxiliary materials and admixtures to obtain internal core materials; mix cementitious materials and auxiliary materials to obtain coating shell materials.
[0045] Specifically, the slag, cementitious materials and auxiliary materials are weighed respectively, added into the mixing equipment to prepare the mixture, and the admixture is added and mixed evenly during the mixing process to obtain the internal core material; the evenly mixed internal core material is sent to the digestion bin, and after digestion for 1-3 hours, it enters the powder mixing system to further disperse the dispersed material. At the same time, part of the cementitious materials and auxiliary materials are weighed, and after being mixed evenly, they are used as the coating shell material.
[0046] In some embodiments, the covering shell material comprises 1-5% by weight of the inner core material.
[0047] In some embodiments, in S1, the mixture includes, by weight: 10-80 parts of slag, 5-20 parts of cementitious materials, and 10-30 parts of auxiliary materials.
[0048] In some embodiments, the slag is selected from one or more of shield slag, engineering slag, building slag, and river and lake silt.
[0049] In some embodiments, the cementitious material is selected from one or more of silicate cement, sulphoaluminate cement, slag cement, carbide slag, quicklime, and waste lime.
[0050] In some embodiments, the auxiliary material is selected from one or more of fly ash, quartz tailings, silica mud, slag, concrete powder, metakaolin, china clay, and volcanic ash soil.
[0051] In some embodiments, in step S1, the admixture accounts for 1%-10% of the weight of the mixture (slag, gel material and auxiliary materials).
[0052] In some embodiments, in step S1, the admixture accounts for 2%-8% of the weight of the mixture.
[0053] In some embodiments, in step S1, the weight ratio of the gelling material to the auxiliary material in the coating shell material is (1-5): (5-8).
[0054] In some embodiments, in step S1, the admixtures include: an activator, an activator, an early strength agent, a dehydrating agent, a separating agent, and a homogenizing agent.
[0055] In some embodiments, in step S1, the admixture includes the following components in parts by weight: 20-85 parts of active agent, 1-15 parts of activator, 1-12 parts of early strength agent, 0.5-10 parts of dehydrating agent, 0.5-8 parts of separating agent, and 0.1-7 parts of homogenizing agent.
[0056] In some embodiments, in step S1, the admixture includes the following components in parts by weight: 25-80 parts of active agent, 2-8 parts of activator, 2-8 parts of early strength agent, 1-5 parts of dehydrating agent, 1-5 parts of separating agent, and 1-5 parts of homogenizing agent.
[0057] In some embodiments, the active agent is selected from one or more of silica fume, high calcium fly ash, and quartz sand.
[0058] In some embodiments, the active agent is selected from one or more of high-calcium fly ash and quartz sand.
[0059] In some embodiments, the average particle size of the active agent is 200-1000 mesh, preferably 300-400 mesh.
[0060] In some embodiments, the activator is selected from one or more of sodium sulfate, sodium hydroxide, calcium hydroxide, and sodium silicate.
[0061] In some embodiments, the activator is selected from one or both of sodium hydroxide and sodium silicate.
[0062] In some embodiments, the activator is a mixture of sodium hydroxide and sodium silicate.
[0063] In some embodiments, in the activator, the weight ratio of sodium hydroxide to sodium silicate is 1:0.5-3.5.
[0064] In some embodiments, in the activator, the weight ratio of sodium hydroxide to sodium silicate is 1:1-2.
[0065] In some embodiments, the early strength agent is selected from one or more of gypsum, desulfurized gypsum, calcium carbonate, triethanolamine, and calcium aluminate.
[0066] In some embodiments, the dehydrating agent is selected from one or more of polyacrylamide, potassium aluminum sulfate dodecahydrate, aluminum chloride, and polyferric chloride.
[0067] In some embodiments, the separating agent is selected from one or more of tartaric acid, sodium polyalkylphenol, sodium methyl silicate, and calcium stearate.
[0068] In some embodiments, the leveling agent is selected from one or more of cellulose ether, lignin, naphthalene sulfonate formaldehyde condensate, and polycarboxylic acid.
[0069] In some embodiments, the preparation method of the admixture is: after mixing the activator, the stimulant, the early strength agent, the dehydrating agent, the separating agent, and the homogenizing agent, the mixture is ground into powder to a particle size of ≤0.075 mm.
[0070] S2, the internal core material is made into a ceramsite ball core through an extrusion granulation molding process; Specifically, the dispersed inner core material is transported to a granulator, and granulated using a double-roll granulation device, a disc granulation device or an extrusion granulation device to obtain a ceramsite core; during the granulation process, 1-20% of water is added.
[0071] S3, coating the coating shell material on the surface of the ceramsite core to obtain a ceramsite green body; Specifically, the ceramsite core is sent to a shaping machine, the ceramsite shape is further optimized by the shaping machine, and the coating shell material is sprayed at the same time so that the coating shell material is evenly distributed on the ceramsite core to obtain a ceramsite green body.
[0072] S4. The unburned expanded clay pellets are obtained through curing.
[0073] In some embodiments, in step S4, the curing includes pre-curing and autoclave curing.
[0074] In some embodiments, in step S4, pre-curing is to stack the shaped ceramsite green body into a pallet cart, transport the pallet cart to a curing room, and pre-curing for 1-24 hours at a temperature of 20-80°C and a humidity of 20-95%.
[0075] In some embodiments, in step S4, the autoclave curing is to send the pre-cured ceramsite into a hydrothermal kettle, close the kettle door, and introduce water vapor until the pressure in the kettle is 0.5-1.0 MPa, and keep the system at 150-200°C for 5-8 hours. During the reaction, gas is replenished as needed. After the reaction is completed, the gas is exhausted to normal pressure, the reactor is opened, and the temperature is lowered to obtain the product ceramsite.
[0076] Example The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0077] Preparation Example Component tests were conducted on the selected shield slag, auxiliary materials and cementitious materials. The test results are shown in Table 1-4.
[0078] The moisture content of the slag is 23.1%. Through XRF analysis, its chemical composition and its weight percentage are shown in Table 1.
[0079] Table 1 Main element composition of shield tunneling soil
[0080] The auxiliary material is fly ash from a coal chemical plant. Through XRF analysis, its chemical composition and weight percentage are shown in Table 2: Table 2 Main element composition of fly ash
[0081] The cementitious material is ordinary Portland cement from the building material yard. Through XRF analysis, its chemical composition and weight percentage are shown in Table 3: Table 3 Main element composition of cement
[0082] Another cementitious material is quicklime from the building material yard. Through XRF analysis, its chemical composition and weight percentage are shown in Table 4: Table 4 Main element composition of lime
[0083] Example 1 A kind of slag unburned ceramsite, and its preparation method is: S1. By weight, 60 parts of slag, 25 parts of fly ash, 12 parts of cement and 3 parts of lime are mixed to obtain a mixture, and an admixture accounting for 2% of the mass of the mixture is added and stirred evenly to obtain an internal core material.
[0084] The admixture is prepared by the following method: 50 parts of active agent (high calcium fly ash, 325 mesh), 5 parts of activator (2.5 parts of sodium hydroxide, 2.5 parts of sodium silicate), 5 parts of early strength agent (triethanolamine), 3 parts of dehydrating agent (polyacrylamide), 3 parts of separating agent (sodium methyl silicate), and 3 parts of homogenizing agent (naphthalenesulfonate formaldehyde condensate) are mixed and ground to a particle size of ≤0.075 mm.
[0085] Subsequently, a coating shell material was prepared, which consisted of 30 parts of cement and 70 parts of fly ash, and the coating shell material was obtained by uniformly mixing.
[0086] The internal core material is sent to the digestion bin for digestion for 3 hours. After the digestion is completed, it goes through the powder mixing section to obtain the dispersed internal core material.
[0087] S2. The dispersed inner core material is transported to the disc granulator. As the disc rotates, the particle size increases continuously to obtain the expanded clay ball core. During the granulation process, 2% of water is added.
[0088] S3, sending the ceramsite core into a shaping machine, and as the drum rotates, the coating shell material prepared in S1 is sprinkled in to coat the ceramsite core to obtain a ceramsite green body, wherein the coating shell material accounts for 2% of the weight of the internal core material.
[0089] S4. The unburned expanded clay pellets are obtained by pre-curing and autoclaving.
[0090] Specifically, the ceramsite green body is piled into a pallet trolley, sent into a curing room, and cured for 3 hours in an environment of a temperature of 60° C. and a humidity of 90.00% to obtain a ceramsite green body; Subsequently, the ceramsite blank is sent to an autoclave curing device, water vapor is introduced into the autoclave curing device, and the reaction is carried out at 1.0 MPa and 180° C. for 6 hours to obtain the ceramsite product.
[0091] Example 2 Example 2 is basically the same as Example 1, with the main difference being that in step S1, the added admixture accounts for 5% of the weight of the mixture (60 parts of slag, 25 parts of fly ash, 12 parts of cement, and 3 parts of lime).
[0092] Example 3 Example 3 is basically the same as Example 1, the main difference being that in step S1, the added admixture accounts for 8% of the weight of the mixture (60 parts of slag, 25 parts of fly ash, 12 parts of cement, and 3 parts of lime).
[0093] Example 4 Example 4 is basically the same as Example 1, the main difference being that in step S1, the added admixture accounts for 1% of the weight of the mixture (60 parts of slag, 25 parts of fly ash, 12 parts of cement, and 3 parts of lime).
[0094] Example 5 Example 5 is basically the same as Example 1, the main difference being that in step S1, the added admixture accounts for 10% of the weight of the mixture (60 parts of slag, 25 parts of fly ash, 12 parts of cement, and 3 parts of lime).
[0095] Example 6 This Example 6 is basically the same as Example 1, with the main difference being that the activator used in preparing the admixture in this Example is silica fume, which replaces the high-calcium fly ash in Example 1.
[0096] Example 7 This Example 7 is basically the same as Example 1, with the main difference being that in the preparation of the admixture in this Example, the activator is a mixture of sodium hydroxide and sodium silicate in a mass ratio of 1:0.5.
[0097] Example 8 This Example 8 is basically the same as Example 1, with the main difference being that in the preparation of the admixture in this example, the activator is a mixture of sodium hydroxide and sodium silicate in a mass ratio of 1:3.
[0098] Example 9 This Example 9 is basically the same as Example 1, with the main difference being that the early strength agent used in preparing the admixture in this Example is desulfurized gypsum, replacing the triethanolamine in Example 1.
[0099] Example 10 This Example 10 is basically the same as Example 1, with the main difference being that the dehydrating agent used in preparing the admixture in this Example is aluminum chloride, which replaces the polyacrylamide in Example 1.
[0100] Embodiment 11 This Example 11 is basically the same as Example 1, with the main difference being that the separating agent used in preparing the admixture in this Example is calcium stearate, replacing the sodium methyl silicate in Example 1.
[0101] Example 12 This Example 12 is basically the same as Example 1, with the main difference being that the leveling agent used to prepare the admixture in this Example is polycarboxylic acid, replacing the naphthalenesulfonate formaldehyde condensate in Example 1.
[0102] Embodiment 13 The admixtures are calculated by weight, and the raw materials for preparation include: 25.5 parts of active agent, 2.6 parts of activator, 2.6 parts of early strength agent, 1.5 parts of dehydrating agent, 1.5 parts of separating agent, and 1.5 parts of homogenizing agent.
[0103] Among them, the active agent is high-calcium fly ash with a particle size of 300 meshes; the activator is sodium hydroxide and sodium silicate with a weight ratio of 1:2; the early strength agent is triethanolamine; the dehydrating agent is polyacrylamide; the separating agent is sodium methyl silicate; and the homogenizing agent is naphthalenesulfonate formaldehyde condensate.
[0104] The preparation method of the admixture is the same as that of Example 1.
[0105] The preparation method of the slag unfired ceramsite is the same as that in Example 1.
[0106] Embodiment 14 The admixtures are calculated by weight, and the raw materials for preparation include: 80 parts of active agent, 8 parts of stimulator, 8 parts of early strength agent, 4.8 parts of dehydrating agent, 4.8 parts of separating agent, and 4.8 parts of homogenizing agent.
[0107] Among them, the activator is high-calcium fly ash with a particle size of 350 mesh; the activator is sodium hydroxide and sodium silicate with a weight ratio of 1:1.5; the early strength agent is triethanolamine; the dehydrating agent is polyacrylamide; the separating agent is sodium methyl silicate; and the homogenizing agent is naphthalenesulfonate formaldehyde condensate.
[0108] The preparation method of the admixture is the same as that of Example 1.
[0109] The preparation method of the slag unfired ceramsite is the same as that in Example 1.
[0110] Embodiment 15 This Example 15 is basically the same as Example 3, the main difference being that in this example, the hydrothermal reaction temperature is 150° C. and the reaction time is 6 h.
[0111] Example 16 This Example 16 is basically the same as Example 3, with the main difference being that in this example, the hydrothermal reaction temperature is 200° C. and the reaction time is 6 h.
[0112] Test Case The performance of the ceramsite prepared in Examples 1-16 was tested, and the cylinder compressive strength, bulk density, and water absorption were measured in accordance with GB / T17431-2010 "Light Aggregates and Test Methods Thereof". The test results are shown in Table 5 below: Table 5 Performance data of ceramsite products
[0113] From the above experimental results, different proportions of admixtures are used in Examples 1-5. As the amount of admixture added increases, the cylinder pressure strength of ceramsite increases and the water absorption rate decreases. In terms of comprehensive ceramsite performance, the most suitable ratio of admixture to mixture in Example 2 is 5%. The effect is the worst in Example 4 due to the lowest admixture content. Although the cylinder pressure strength in Examples 3 and 5 increases, the overall trend slows down.
[0114] From the data in Examples 1 and 6, it can be seen that with the change of the activator in the admixture, the cylinder pressure strength of the ceramsite decreases and the water absorption rate increases; this may be because: compared with fly ash, although silica fume has the advantages of highly active silicon dioxide and fine particle size, it has no activity itself, and its water absorption and dispersion effects are poor, so its beneficial effect on the system is slightly inferior.
[0115] From the data in Examples 1, 7, and 8, as the weight ratio of sodium hydroxide and sodium silicate in the activator in the admixture changes, when the proportion of sodium silicate in Example 7 decreases, the cylinder pressure strength of the ceramsite decreases and the water absorption rate increases, and when the proportion of sodium silicate in Example 8 increases, the cylinder pressure strength decreases and the water absorption rate increases. This may be due to: when the proportion of sodium silicate in the activator is too small, although the proportion of sodium hydroxide increases and the alkali activation effect of the system is better, the lower amount of sodium silicate causes the active siliceous composition in the system to decrease, and it is impossible to cooperate with sodium hydroxide to form a better active activation effect, the proportion of active silica gel in the system is reduced, and the promotion effect on the hydrothermal reaction is reduced; and the lower amount of sodium silicate also leads to the deterioration of the overall cementing performance of the system, so the cylinder pressure strength and water absorption rate of the obtained ceramsite are reduced. When the proportion of sodium hydroxide in the stimulator is too small, the alkalinity of the system decreases and the stimulating effect of the admixture on the system is limited; at the same time, the amount of sodium silicate in the admixture is too high, and silica gel is easily formed inside the system, which will significantly increase the viscosity of the admixture. Excessive bonding performance can easily lead to adhesion of the internal core material and uneven material distribution, so the performance of the expanded clay decreases.
[0116] From the data in Examples 1 and 9, it can be seen that with the change of the early strength agent in the admixture, the cylinder compressive strength of the ceramsite decreases and the water absorption rate increases; it may be because when triethanolamine is used as an early strength agent, it has good early strength performance and can also delay the coagulation of the cementitious material, so that the ceramsite green body can be fully hydrated during the curing stage, the excellent activity of the cementitious material can be exerted, the alkalinity inside the system can be increased to improve the degree of hydrothermal reaction, so that the cylinder compressive strength of the ceramsite is better; while desulfurized gypsum as an early strength agent can only react with calcium aluminate in the cementitious material. Although it can make the slag harden quickly to achieve internal dispersion of large particles, it has no promoting effect on the hydrothermal reaction, which is manifested as a decrease in the cylinder compressive strength, indicating that the internal reaction degree is low, and the solidification of the slag is weak, resulting in an increase in water absorption.
[0117] From the data in Examples 1 and 10, it can be seen that with the change of the dehydrating agent in the admixture, the cylinder pressure strength of the expanded clay decreases and the water absorption rate increases; this may be because polyacrylamide can quickly flocculate and thus improve the dispersion of the slag; and aluminum chloride, as an inorganic material, although it can achieve the removal of moisture inside the slag, its efficiency is limited compared to organic polymer materials, and its dehydration effect is biased, resulting in obvious differences in the dispersion state of the mixture, making it difficult to release more active substances to participate in the hydrothermal reaction.
[0118] From the data in Examples 1 and 11, it can be seen that with the change of the separating agent in the admixture, the cylinder pressure strength of the expanded clay decreases and the water absorption rate increases; this may be because the separating agent is a hydrophobic raw material, which forms a hydrophobic film on the surface of the slag, effectively isolating the combination of free water and the slag during the digestion process, so that the mixture maintains a good dispersion state; sodium methyl silicate has good permeability in addition to calcium stearate, and can penetrate into the interior of the slag to achieve further dispersion of the microstructure, so compared with Example 11, the performance of the expanded clay obtained in Example 1 is better.
[0119] From the data in Examples 1 and 12, with the change of the homogenizer in the admixture, the cylinder compressive strength of the ceramsite decreases and the water absorption rate increases. This may be because the addition of polycarboxylic acid can change the surface charge of the slag, form electrostatic repulsion with water molecules, and promote the dispersion of the slag and the cementitious material. However, due to the strong adsorption effect of the clay component inside the slag on the polycarboxylic acid particles, the polycarboxylic acid fails to find its good electrostatic steric hindrance effect inside the system; while the adsorption effect of clay on naphthalenesulfonate formaldehyde condensate is poor, which makes its dispersion effect better, so that the cylinder compressive strength of the ceramsite increases and the water absorption rate decreases.
[0120] Examples 13 and 14 both belong to the formulations within the protection scope of the present application, and have better cylinder pressure strength and lower water absorption.
[0121] From the data of Examples 3, 15, and 16, the change of the hydrothermal process has a certain impact on the product. The performance of the product fluctuates at different reaction temperatures. The cylinder pressure strength of the ceramsite first rises rapidly and then gradually stabilizes with the increase of the reaction temperature, and the water absorption first decreases and then remains basically unchanged. It may be because the hydrothermal reaction is relatively slow at low temperatures, the dissolution of silicon and calcium ions is limited, and the products formed by the hydrothermal reaction are relatively small, which limits the performance of the ceramsite; while at high temperatures, the dissolution of ions is better, but the actual proportion of active ingredients in the system is basically the same. The increase in temperature can only increase the reaction rate in the early stage, and there is no obvious gain for the later reaction, and it cannot increase the output of the hydrothermal product, so the performance of the ceramsite is not significantly improved.
[0122] Therefore, the present invention adds an admixture prepared by mixing an activator, an activator, an early strength agent, a dehydrating agent, a separating agent and a homogenizing agent to disperse the slag raw material. Through the joint action of the early strength agent, the dehydrating agent, the separating agent and the homogenizing agent, the bound water inside the slag is released, so that the slag particles and the auxiliary materials and the cementitious materials are evenly dispersed, the particle size distribution of the mixture is effectively controlled, and the internal activity of the slag is further released; combined with the effects of the activator and the activator, on the one hand, the siliceous activity inside the slag is supplemented to provide seeds for the hydrothermal synthesis at the back end, which can accelerate the synthesis of the hydrothermal product and thus improve the product performance; on the other hand, the siliceous activity inside the slag is promoted by the activator, so that the inert silica inside the slag that is not easy to participate in the reaction is stimulated, and the activity of the slag is improved from the raw material end, so that the prepared expanded clay has high cylinder compressive strength and low water absorption rate, and can be used as a high-quality building material product to achieve efficient resource utilization of the slag.
[0123] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A kind of slag unburned ceramsite, characterized in that: It comprises an inner core and a covering shell, wherein the inner core comprises a mixture and an admixture; The admixture accounts for 1%-10% of the weight of the mixture; The mixture includes: slag, cementitious materials and auxiliary materials; The additives include: an activator, an activator, an early strength agent, a dehydrating agent, a separating agent and a homogenizing agent.
2. The unburned clay ceramsite according to claim 1, characterized in that: The admixture accounts for 2%-8% of the weight of the mixture; The coating shell includes: a gel material and an auxiliary material, and the weight ratio of the gel material to the auxiliary material is (1-5): (5-8).
3. The slag unburned ceramsite according to claim 1, characterized in that: The admixture includes the following components in parts by weight: 20-85 parts of active agent, 1-15 parts of activator, 1-12 parts of early strength agent, 0.5-10 parts of dehydrating agent, 0.5-8 parts of separating agent, and 0.1-7 parts of homogenizing agent; The active agent is selected from one or more of silica fume, high calcium fly ash and quartz sand; The activator is selected from one or more of sodium sulfate, sodium hydroxide, calcium hydroxide, and sodium silicate; The early strength agent is selected from one or more of gypsum, desulfurized gypsum, calcium carbonate, triethanolamine, and calcium aluminate; The dehydrating agent is selected from one or more of polyacrylamide, potassium aluminum sulfate dodecahydrate, aluminum chloride, and polyferric chloride; The separating agent is selected from one or more of tartaric acid, sodium alkylphenol polyate, sodium methyl silicate, and calcium stearate; The leveling agent is selected from one or more of cellulose ether, lignin, naphthalenesulfonate formaldehyde condensate, and polycarboxylic acid.
4. The slag unburned ceramsite according to claim 1, characterized in that: The active agent is selected from one or more of high-calcium fly ash and quartz sand; the average particle size of the active agent is 200-1000 mesh; The activator is selected from one or both of sodium hydroxide and sodium silicate.
5. The slag unburned ceramsite according to claim 1, characterized in that: The average particle size of the active agent is 300-400 mesh; The activator is a mixture of sodium hydroxide and sodium silicate, and the weight ratio of the sodium hydroxide to the sodium silicate is 1:0.5-3.
5.
6. The unburned clay ceramsite according to claim 1, characterized in that: The activator is a mixture of sodium hydroxide and sodium silicate, and the weight ratio of the sodium hydroxide to the sodium silicate is 1:1-2; The preparation method of the admixture is as follows: after mixing the activator, the stimulant, the early strength agent, the dehydrating agent, the separating agent and the homogenizing agent, the mixture is ground to a particle size of ≤0.075 mm.
7. The unburned clay ceramsite according to claim 1, characterized in that: The mixture comprises the following components in parts by weight: 10-80 parts of slag, 5-20 parts of cementitious materials, and 10-30 parts of auxiliary materials; The slag is selected from one or more of shield slag, engineering slag, building slag, river and lake silt; The cementitious material is selected from one or more of silicate cement, sulphoaluminate cement, slag cement, carbide slag, quicklime and waste lime; The auxiliary material is selected from one or more of fly ash, quartz tailings, silicon mud, slag, concrete powder, metakaolin, porcelain clay, and volcanic ash soil.
8. A method for preparing the unburned clay ceramsite according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Mix slag, cementitious materials, auxiliary materials and admixtures to obtain internal core materials; mix cementitious materials and auxiliary materials to obtain coating shell materials; S2, the internal core material is made into a ceramsite ball core through an extrusion granulation molding process; S3, coating the coating shell material on the surface of the ceramsite core to obtain a ceramsite green body; S4. The unburned expanded clay pellets are obtained through curing.
9. The method for preparing unburned ceramsite from slag according to claim 8, characterized in that: In step S1, the coating shell material accounts for 1-5% of the weight of the internal core material: Step S1 also includes the following steps: the internal core material is sent into a digestion bin for digestion, and then enters a powder mixing system for dispersion.
10. The method for preparing unburned ceramsite from slag according to claim 8, characterized in that: In step S4, curing includes pre-curing and autoclaving; The curing temperature of the pre-curing is 20-80°C, the curing humidity is 20-95%, and the curing time is 1-24h; The reaction temperature of the autoclave curing is 150-200° C., the reaction pressure is 0.5-1.0 MPa, and the reaction time is 5-8 hours.
Citation Information
Patent Citations
Rail shield muck unburned and non-autoclaved ceramsite and preparation method thereof
CN104710156A
High-strength unfired ceramsite and preparation method thereof
CN111170710A
Preparation method of high-content and high-strength fly ash non-sintered ceramsite
CN112745071A
Unfired ceramsite and preparation method thereof
CN113860843A
High-strength residue-soil non-sintered ceramsite and preparation method thereof
CN116462433A
Cited By
Core-shell type solid waste-based functional aggregate as well as preparation method and application thereof
CN119430846A